Integrating Artificial Intelligence as an Academic Learning Tool for University Students: Sociological Implications - Akindehinde, Ayobamidele Peter; Omorogieva, Esther Pamela (NIU Journal of Social Sciences, 2025)
This study assessed the generality of the integration of Artificial Intelligence (AI) as an academic learning tool for university students by analyzing the key themes including enhanced student engagement, improved academic performance and potential shifts in knowledge dynamics. It specifically, discussed trends in the development of artificial intelligence, AI impact on university students’ academic performance, the sociological implications of artificial intelligence, and some of its challenges and suggestion for AI usage advancement among the students and students-teachers during teaching and learning were also discussed. The study concluded that, despite the fact that these technologies are becoming more prominent in higher education, not all students enjoy equal access to them. Differences in technological infrastructure, institutional readiness, and digital literacy continue to influence how effectively students can benefit from AI. Although AI's promise to enhance learning outcomes is well acknowledged in theory, practical research on its real-world impact on academic performance, particularly in the context of developing nations remains limited. Keywords: Artificial Intelligence, Sociological Implications